Fiber Bragg gratings as transient thermal gradient sensors - Hackney, Drew A; Peters, Kara J; Black, Richard J; Costa, Joannes M; Moslehi, Behzad (Optical engineering, 2016)
We experimentally subject a fiber Bragg grating to an unknown, variable temperature gradient. We use the full-spectral response of the grating to determine the magnitude of the gradient over the length of the grating via the full width at quarter maximum bandwidth. The experimental bandwidth and spectrum deformation were compared with a numerical model consisting of an analytical heat transfer model, a finite element analysis model, and the transfer matrix (T-matrix) method. The numerical model showed excellent agreement with the experimental results when the T-matrix method was modified to include the slope of the gradient in addition to the magnitude of the gradient.